Interfacial Phonon Transport Through Si/Ge Multilayer Film Using Monte Carlo Scheme With Spectral Transmissivity - Ran, Xin; Guo, Yangyu; Hu, Zhiyu; Wang, Moran (Frontiers in Energy Research, 2018)
The knowledge of interfacial phonon transport accounting for detailed phonon spectral properties is desired because of its importance for design of nanoscale energy systems. In this work, we investigate the interfacial phonon transport through Si/Ge multilayer films using an efficient Monte Carlo scheme with spectral transmissivity, which is validated for cross-plane phonon transport through both Si/Ge single-layer and Si/Ge bi-layer thin films by comparing with the discrete-ordinates solution. Different thermal boundary conductances between even the same material pair are declared at different interfaces within the multilayer system. Furthermore, the thermal boundary conductances at different interfaces show different trends with varying total system size, with the variation slope, very different as well. The results are much different from those in the bi-layer thin film or periodic superlattice. These unusual behaviors can be attributed to the combined interfacial local non-equilibrium effect and constraint effect from other interfaces.